Sequential vapour ablation of adjacent segments in canine lung. (June 2014) - Henne, Erik; Barry, Robert; Mest, Robert; Snell, Gregory
Abstract Introduction: Vapour ablation is used to create lung volume reduction for emphysema patients to improve lung function and quality of life. This study characterises effects of vapour ablation treatment in lung segments within a lobe that are adjacent to lung segments previously treated with vapour in a healthy canine model. Because emphysema is a progressive disease, subsequent treatments could offer continued benefit to the patient. Method: Six healthy canines were treated with vapour at 8.5 cal/g in one upper lobe segment. After a 4-week healing period, the adjacent segment was treated. After a second 4-week healing period, necropsy was performed and the tissue inspected. Clinical effects were monitored during each healing period. Results: Each treatment was well tolerated and no significant abnormalities were observed during the healing phases, including death, pneumothorax, or major decline in health status. Animal health, oxygenation changes, pathology, and airway changes were monitored during the study. Analysis of these end points showed no difference in changes after treatment 2 as compared to changes after treatment 1. Conclusion: In this model, there was no evidence of increased or different clinical observations after a second adjacent vapour ablation. It was not possible to differentiate between the clinical effects of treatment 1 and the clinical effects of treatment 2. These results support investigation of sequential adjacent segmental vapour treatments in humans.